Ultrasound-Guided Steroid Injection to the Residual Limb Stalk Facilitated the Treatment of a Painful Above-Knee Residual Limb Neuroma. Issue 1 (3rd April 2015) - Buntragulpoontawee, Montana; Hung, Chen-Yu; Rapipong, Jeeranan; Chang, Ke-Vin
Abstract: Background : A post-amputation neuroma can cause chronic persistent residual limb pain in amputees. Painful neuromas are difficult to identify with clinical examination alone because most of them are deeply buried. Findings : We presented a patient with pain over his left above-knee residual limb, aggravating 40 years after amputation. The pain originated from a previously undetected neuroma and was relieved following a single dose of ultrasound-guided steroid injection to the neuroma stalk. Conclusion : Ultrasound is beneficial for differentiating the cause of residual limb pain and a single corticosteroid injection targeting the neuroma stalk appeared effective for pain relief.